2001
DOI: 10.1172/jci11685
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin inhibits prostate cancer–induced osteoclastogenesis and prevents prostate tumor growth in the bone

Abstract: IntroductionProstate cancer is the most frequently diagnosed cancer in men and the second leading cause of cancer death among men in the US. The most common site of prostate cancer metastasis is the bone, with up to 84% of patients demonstrating skeletal metastases (1). While initially thought to be primarily osteoblastic, it is now recognized that prostate cancer skeletal metastases have an extensive bone resorptive component (2, 3) that is caused primarily by osteoclasts (4). This accounts, in part, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
363
4
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(399 citation statements)
references
References 43 publications
24
363
4
5
Order By: Relevance
“…Pharmacological inhibition of RANKL using recombinant constructs of either OPG-Fc or RANK-Fc in these models reduces tumor induced osteoclast numbers [18,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of RANKL using recombinant constructs of either OPG-Fc or RANK-Fc in these models reduces tumor induced osteoclast numbers [18,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…1 Inhibitors of bone resorption such as bisphosphonates (BPs), osteoprotegerin (OPG), and metalloproteinase (MMP) inhibitors have been reported to decrease bone resorption associated with bone metastasis and decrease tumor burden in several animal models. [2][3][4][5][6] BPs are currently used to treat osteoporosis, reduce bone metabolic activity in Paget's disease, and control metastatic breast cancer and associated osteolytic bone lesions, as well as metastatic CaP. In a clinical study Diel et al 7 reported that clodronate, a first-generation BP, decreased numbers of both bone and soft tissue metastases in breast cancer patients, suggesting potential direct effects of BPs on metastases in addition to decreased bone lysis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Our current understanding of the pathogenesis of bone metastasis is that various osteotropic malignancies use RANKL-mediated mechanisms to trigger osteoclastic bone resorption. [13][14][15] Michigami et al 16 found that cell interaction between neuroblastoma cells and bone marrow of immunocompromised mice induced RANKL expression in host cells, leading to osteoclast formation and bone metastasis. However, apart from the above-mentioned work, the molecular mechanisms responsible for metastatic osteolysis in neuroblastoma have been poorly investigated, and the exact nature of neuroblastoma-bone interactions remains largely unknown.…”
mentioning
confidence: 99%